INSTITUTIONALIZING THE CONSTITUTIONAL QUESTION AUTHORITY IN THE CONSTITUTIONAL COURT AND POSSIBILITY INSTITUTIONALIZING IN SUPREME COURT - Manurung, Saut Parulian; Suhartono, Slamet; Nasution, Krisnadi (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractThis article aims to analyze and discuss the institutionalization of the idea of a constitutional question at the Constitutional Court, and the possibility of its institutionalization at the Supreme Court. The method used is a statutory approach, a conceptual approach, and a comparative approach. This article takes the position of